Answer:
44
Step-by-step explanation:
k=1: 2*1-4 = -2
k=2: 2*2²-4 = 4
k=3: 2*3²-4 = 14
k=4: 2*4²-4 = 28
-2 + 4 + 14 + 28 = 44
<span>
The standard form of the equation of a circumference is given by the following expression:
</span>
![(x-h)^{2}+(y-k)^{2}=r^{2} \\ \\ where \ (h, k) \ is \ the \ center \ of \ the \ circumference \ and \ r \ the \ radius](https://tex.z-dn.net/?f=%28x-h%29%5E%7B2%7D%2B%28y-k%29%5E%7B2%7D%3Dr%5E%7B2%7D%20%5C%5C%20%5C%5C%20where%20%5C%20%28h%2C%20k%29%20%5C%20is%20%5C%20the%20%5C%20center%20%5C%20of%20%5C%20the%20%5C%20circumference%20%5C%20and%20%5C%20r%20%5C%20the%20%5C%20radius)
<span>
On the other hand,
the general form is given as follows:
</span>
![x^{2}+y^{2}+Dx+Ey+F=0 \\ \\ where: \\ D=-2h, \ E=-2k, \ F=h^{2}+k^{2}-r^{2}](https://tex.z-dn.net/?f=x%5E%7B2%7D%2By%5E%7B2%7D%2BDx%2BEy%2BF%3D0%20%5C%5C%20%5C%5C%20where%3A%20%5C%5C%20D%3D-2h%2C%20%5C%20E%3D-2k%2C%20%5C%20F%3Dh%5E%7B2%7D%2Bk%5E%7B2%7D-r%5E%7B2%7D)
<span>
In this way, we can order the mentioned equations as follows:
Equations in Standard Form: </span>
Equations in General Form:
![\bold{1)} \ x^{2}+y^{2}-4x+12y-20=0 \\ \bold{2)} \ x^{2}+y^{2}+6x-8y-10=0 \\ \bold{3)} \ 3x^{2}+3y^{2}+12x+18y-15=0 \\ \\ If \ we \ divide \ this \ equation \ by \ 3, \ the \ equation \ becomes: \\ x^{2}+y^{2}+4x+6y-5=0 \\ \\ \bold{4)} \ 5x^{2}+5y^{2}-10x+20y-30=0 \\ \\ If \ we \ divide \ this \ equation \ by \ 5, \ the \ equation \ becomes: \\ x^{2}+y^{2}-2x+4y-6=0 \\ \\ \bold{5)} \ 2x^{2}+2y^{2}-24x-16y-8=0 \\ \\ If \ we \ divide \ this \ equation \ by \ 2, \ the \ equation \ becomes: \\ x^{2}+y^{2}-12x-8y-4=0](https://tex.z-dn.net/?f=%5Cbold%7B1%29%7D%20%5C%20x%5E%7B2%7D%2By%5E%7B2%7D-4x%2B12y-20%3D0%20%5C%5C%20%5Cbold%7B2%29%7D%20%5C%20x%5E%7B2%7D%2By%5E%7B2%7D%2B6x-8y-10%3D0%20%5C%5C%20%5Cbold%7B3%29%7D%20%5C%203x%5E%7B2%7D%2B3y%5E%7B2%7D%2B12x%2B18y-15%3D0%20%5C%5C%20%5C%5C%20If%20%5C%20we%20%5C%20divide%20%5C%20this%20%5C%20equation%20%5C%20by%20%5C%203%2C%20%5C%20the%20%5C%20equation%20%5C%20becomes%3A%20%5C%5C%20x%5E%7B2%7D%2By%5E%7B2%7D%2B4x%2B6y-5%3D0%20%5C%5C%20%5C%5C%20%5Cbold%7B4%29%7D%20%5C%205x%5E%7B2%7D%2B5y%5E%7B2%7D-10x%2B20y-30%3D0%20%5C%5C%20%5C%5C%20If%20%5C%20we%20%5C%20divide%20%5C%20this%20%5C%20equation%20%5C%20by%20%5C%205%2C%20%5C%20the%20%5C%20equation%20%5C%20becomes%3A%20%5C%5C%20x%5E%7B2%7D%2By%5E%7B2%7D-2x%2B4y-6%3D0%20%5C%5C%20%5C%5C%20%5Cbold%7B5%29%7D%20%5C%202x%5E%7B2%7D%2B2y%5E%7B2%7D-24x-16y-8%3D0%20%5C%5C%20%5C%5C%20If%20%5C%20we%20%5C%20divide%20%5C%20this%20%5C%20equation%20%5C%20by%20%5C%202%2C%20%5C%20the%20%5C%20equation%20%5C%20becomes%3A%20%5C%5C%20x%5E%7B2%7D%2By%5E%7B2%7D-12x-8y-4%3D0%20)
![\bold{6)} \ x^{2}+y^{2}+2x-12y](https://tex.z-dn.net/?f=%5Cbold%7B6%29%7D%20%5C%20x%5E%7B2%7D%2By%5E%7B2%7D%2B2x-12y)
So let's match each equation:
Then, its general form is:
<em><u>First. a) matches 5)
</u></em>
![\bold{From \ b)} \\ \\ (h,k)=(2,-6),\ r=2\sqrt{15} \\ D=-4, \ E=12 \\ F=-20](https://tex.z-dn.net/?f=%5Cbold%7BFrom%20%5C%20b%29%7D%20%5C%5C%20%5C%5C%20%28h%2Ck%29%3D%282%2C-6%29%2C%5C%20r%3D2%5Csqrt%7B15%7D%20%5C%5C%20D%3D-4%2C%20%5C%20E%3D12%20%5C%5C%20F%3D-20)
Then, its general form is:
<em><u>Second. b) matches 1)
</u></em>
Then, its general form is:
<em><u>Third. c) matches 3)</u></em>
Then, its general form is:
<em><u>Fourth. d) matches 6)</u></em>
Answer:
They rode 14 miles before replacing each horse
Step-by-step explanation:
We will be working under the assumption that all three riders sat on one horse at a time and rode it while the other horses rested.
From the problem, we can understand that the horses were each ridden for the same distance. This means that to get the total distance a horse rode before it was changed, we can divide the total distance by the number of horses that were used for the journey.
Distance each horse rode = 182/ 13 = 14 miles.
Therefore, each horse was ridden for 14 miles before it was changed.
Answer:
the area is 26 the perimetier is 52
Step-by-step explanation:
Answer: Maybe search it up?...I cant rlly see what the question says
Step-by-step explanation: